Accountability of Regional Heads to Regional People’s Representative Council Following the Amendment of the 1945 Constitution - La Ode Muhaimin; Rahmat Taibu; Amrun Kahar (Fakultas Hukum Universitas Lampung, 2025)
Amendments to the 1945 Constitution have reinforced the presidential system at the regional level through the direct election of regional heads and a dismissal mechanism analogous to that of the president. However, key elements of presidentialism in regional governance are obscured by the requirement that regional heads submit an Accountability Report (LKP) to the Regional People’s Representative Council (DPRD), while the DPRD is also positioned within the regional government structure. This research examines, first, how presidential and unitary state perspectives conceptualize the LKP obligation and, second, whether it undermines the DPRD’s role as part of the legislative branch. Using normative legal analysis with juridical and conceptual approaches, the research finds that the relationship between regional heads and the DPRD continues to be framed by unitary state logic, thereby legitimizing central regulations mandating the LKP. In substance, however, this relationship aligns more closely with a presidential framework involving two distinct and coequal regional institutions. The LKP requirement therefore weakens the presidential character of regional governance. Moreover, defining the DPRD as part of the regional executive is conceptually flawed, as it risks implying multiple legislatures in a unitary state. As a representative body, the DPRD belongs to the legislative branch, differing from the DPR only in jurisdiction, and the LKP obligation further obscures this role and conflicts with the principle of checks and balances.